Development of Zr-based metallic glass matrix composites with hybrid reinforcing structures. (October 2021) - Shao, Yuman; Zhang, Zhen; Guo, Wei; Tang, Xuefeng; Lü, Shulin; Chen, Xiaohua; Wu, Shusen
Abstract: The hybrid reinforcing structures, which contain Ta-rich particles, B2–CuZr and B19′-CuZr phases, have been successfully introduced into a Zr-based metallic glass matrix by doping with Ta. Due to the high melting temperature of Ta, the Ta-rich particles precipitate firstly, and contribute to the homogeneous distribution of B2 and B19′-CuZr phases by acting as their nuclei to form a core-shell reinforcing structure. The plasticity of the present hybrid structures reinforced metallic glass matrix composites have been improved a lot when compared with the monolithic counterparts. The rapid propagation of main shear bands in the matrix is considered to be hindered by the presence of the hybrid reinforcing structures. The martensitic transformation of B2–CuZr phases and the deformation of the Ta-rich particles cooperatively contribute to the plasticity and work-hardening behavior of the composites. The simulation results suggest that the core phase (Ta-rich particle) bears the highest strain and triggers the initiation of shear bands. Highlights: Hybrid reinforcing structure is induced by doping with Ta into a metallic glass. Ta-rich phase acts as the effective nuclei for B2–CuZr and B19′-CuZr phases. Dispersion of the reinforcing core-shell reinforcing structures is homogeneous. Composites show improved strength and plasticity at room temperature. Cooperative reinforcing mechanism contributes to the overall plasticity.